Barriers and enablers to the use of venous leg ulcer clinical practice guidelines in Australian primary care: A qualitative study using the theoretical domains framework. (March 2020) - Weller, C.D.; Richards, C.; Turnour, L.; Patey, A.M.; Russell, G.; Team, V.
Abstract: Background: Venous leg ulcers represent the most common chronic wound problem managed in Australian primary care. Despite the prevalence of the condition, there is an evidence-practice gap in both diagnosis and management of venous leg ulcers. Objective: We used the Theoretical Domains Framework to identify barriers and enablers perceived by primary care practitioners in implementing venous leg ulcer guidelines in clinical practice. Design: We collected data to explore the experiences of practice nurses and general practitioners related to their use of clinical practice guidelines in management of venous leg ulcers. Setting(s): We recruited participants from primary care settings located in metropolitan and rural areas across Victoria, Australia. Participants: We recruited general practitioners (15) and practice nurses (20). Methods: We conducted 35 semi-structured face-to-face and telephone interviews. Content analysis of health practitioners' statements was performed and barriers to implementing clinical practice guidelines were mapped across the Theoretical Domains Framework theoretical domains. Results: Six main domains from the Theoretical Domains Framework (Environmental context and resources, Knowledge, Skills, Social influences, Social/Professional Role and Identity and Belief about Capabilities) best explained these barriers and enablers. Many participants were not aware of venous leg ulcer clinical practice guidelines. Those that were aware, stated that finding and accessing guidelines was challenging and most participants relied on other sources of information. Venous leg ulcer management was greatly influenced by professional experience and suggestions from colleagues. Other barriers included busy clinical practice, absence of handheld Doppler ultrasonography, insufficient skills and a lack of confidence related to the use of technology to rule out arterial involvement prior to compression application, a particular skill related to venous leg ulcer management that will impact on healing outcomes. Conclusions: We identified a number of barriers and the lack of enablers that influence the uptake of venous leg ulcer clinical practice guidelines in primary care. This paper adds a theoretically sound, systematic approach for understanding and addressing the behaviour change required to improve translation of venous leg ulcer clinical practice guidelines in clinical practice. Tweetable abstract: The need to optimise venous leg ulcer clinical practice guidelines (CPG) has never been greater as the current estimate of health cost is AUD3billion and increasing due to rising epidemics of diabetes and obesity. We found most primary care health practitioners are unaware of CPG and this will impact on health and healing outcomes in Australian primary care.